Cyber Security Awareness Webinar Preparing - Mritha, Ramalingam (Faculty of Computing, 2021)
PEKAN, 23September 2021 - A Cyber Security Awareness Webinar: Preparing Against Security Threats was organized and conducted virtually over Google Meet with Facebook live broadcast by Community College Paya Besar, Gambang, Pahang.